Contra la gravedad sin gracia : Alexander Calder en el Guggenheim Bilbao - Ramirez, Juan Antonio (2003)
Acerca de la muestra del escultor en Bilbao
Keywords: EXPOSICIONES; ARTE; ESCULTURA; BILBAO; CALDER, ALEXANDER; ESPAÑA